Optimalisasi Nilai Ekspor Ikan Tuna Hs 160414 Ke Italia Dengan Metode Mamdani - Luthfia Rohimah; Sinta Rukiastiandari; Juarni Siregar (Universitas Bina Sarana Informatika, 2019)
The decline in oil and gas exports since 1990 requires the government to take policy steps to increase non-oil exports so that state revenues continue to grow. One of the non-oil and gas exports that is a mainstay of Indonesia is tunat fish which has the HS code 160414. Italy is a country where the demand for tuna is quite high. In order to maximize the value of Indonesian tuna exports to Italy, a method is needed to optimize the value of Indonesian tuna exports to Italy. The purpose of this study was to find out the best method to predict the value of tuna exports to Italy in the application of fuzzy logic in order to optimize the value of exports. The results showed that the Mamdani method was a good method. The Mamdani method has results that are close to the actual results with an error rate of 1.1%, so the Mamdani method can be used as the recommended method in optimizing the optimal amount of export HS 160414 Indonesia to Italy.